Evaluating capacity-building for mental health system strengthening in low- and middle-income countries for service users and caregivers, service planners and researchers. (31st August 2017) - Hanlon, C.; Semrau, M.; Alem, A.; Abayneh, S.; Abdulmalik, J.; Docrat, S.; Evans-Lacko, S.; Gureje, O.; Jordans, M.; Lempp, H.; Mugisha, J.; Petersen, I.; et al.
Abstract : Efforts to support the scale-up of integrated mental health care in low- and middle-income countries (LMICs) need to focus on building human resource capacity in health system strengthening, as well as in the direct provision of mental health care. In a companion editorial, we describe a range of capacity-building activities that are being implemented by a multi-country research consortium (Emerald: Emerging mental health systems in low- and middle-income countries) for (1) service users and caregivers, (2) service planners and policy-makers and (3) researchers in six LMICs (Ethiopia, India, Nepal, Nigeria, South Africa and Uganda). In this paper, we focus on the methodology being used to evaluate the impact of capacity-building in these three target groups. We first review the evidence base for approaches to evaluation of capacity-building, highlighting the gaps in this area. We then describe the adaptation of best practice for the Emerald capacity-building evaluation. The resulting mixed method evaluation framework was tailored to each target group and to each country context. We identified a need to expand the evidence base on indicators of successful capacity-building across the different target groups. To address this, we developed an evaluation plan to measure the adequacy and usefulness of quantitative capacity-building indicators when compared with qualitative evaluation. We argue that evaluation needs to be an integral part of capacity-building activities and that expertise needs to be built in methods of evaluation. The Emerald evaluation provides a potential model for capacity-building evaluation across key stakeholder groups and promises to extend understanding of useful indicators of success.